Anti-drug antibody detection with label-free electrolyte-gated organic field-effect transistors. Issue 3 (16th December 2020) - Sensi, Matteo; Berto, Marcello; Gentile, Sara; Pinti, Marcello; Conti, Andrea; Pellacani, Giovanni; Salvarani, Carlo; Cossarizza, Andrea; Bortolotti, Carlo Augusto; Biscarini, Fabio
Abstract : The first label-free EGOFET immunosensor able to quantitatively detect anti-drug antibodies against Nivolumab, with a LOD of 100 fM. Abstract : The efficacy of immunotherapy can be undermined by the development of an immune response against a drug/antibody mediated by anti-drug antibodies (ADAs) in treated patients. We present the first label-free EGOFET immunosensor that integrates a biological drug, Nivolumab (Opdivo©), as a specific recognition moiety to quantitatively and selectively detect ADAs against the drug. The limit of detection is 100 fM. This demonstration is a prelude to the detection of ADAs in a clinical setting in the treatment of different pathologies, and it also enables rapid screening of biological drugs for immunogenicity.